Effect of environmentally-friendly flame retardants on fire resistance and mechanical properties of rigid polyurethane foam - Czech-Polak, J.; Przybyszewski, B.; Heneczkowski, M.; Czulak, A.; Gude, M. (Polimery, 2021)
In this paper the new compositions of polyurethane foams with reduced flammability containing environmentally friendly flame retardants, such as ammonium polyphosphate, melamine pyrophosphate, triethyl phosphate, bentonite and expanded graphite obtained with long fiber injection (LFI) method have been presented. The effect of the addition of various flame retardants and their mixtures on the fire resistance and mechanical properties of the foams has been determined. An improvement in fire resistance of the modified polyurethane compositions has been observed. Manufactured polyurethane foams containing flame retardants have been classified as materials with flammability class V-0. The addition of flame retardants has not significantly deteriorated mechanical properties of the investigated materials.